Effect of deficit irrigation on the growth and yield of peanuts (Arachis hypogaea (L.) Merr.) compared to AquaCrop model simulation - Febery Hery Suandana; Cahyoadi Bowo; Sigit Soeparjono (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2023)
The availability of irrigation water during the growing season reflects on the potential yield at the end of the peanuts’ growing season. Monitoring water availability is essential to optimize production. This study aimed to identify the effect of irrigation water on peanuts (Arachis hypogaea (L.) Merr.) under various irrigation conditions between actual and simulated AquaCrop. The research was conducted in the experimental field utilizing four irrigation treatments which were 60%, 80%, 100% of field capacity (FC), and standard irrigation. The correlation results between the actual and simulated ones showed that the R2 value was 0.974–0.990 for the canopy cover parameter, 0.026–0.534 for ETc, and 0.542-0.554 for production. Comparison between actual and simulated AquaCrop showed Root Mean Square Error (RMSE) values of 5.08–9.74 for canopy cover parameters, 1.11–3.12 for ETc, and 0.82–1.09 for production. Welch test statistical analysis indicated values of 2.31–5.52 for plant biomass and 0.04–3.98 for dry pod yields. The AquaCrop simulation accurately predicted canopy cover at 80% irrigation treatment compared to 60%, 100%, and standard irrigation treatments. Parameter of ETc in AquaCrop simulations showed inaccurate predictions for biomass production and pod dry weight when compared with actual results on all irrigation treatments.